Effects of commercial isotonic sports drinks during intermittent exertion - Zart, S.; Fröhlich, M. (International Journal of Kinesiology & Sports Science, 2019)
Background: Carbohydrate-electrolyte drinks support performance and recovery during athletic activities. The impact of these isotonic drinks is usually verified by means of placebos without energy. Objective: We checked the extent to which commercial sports drinks may be superior to a syrup-water mixture, similar in calorific value, during an intermittent exertion. Method: In a cross-sectional study, three homogeneously parallelized groups, including a total of 35 test subjects, performed full-strain endurance and speed tests (5,000 m, 3,000 m, 1,500 m, 800 m, 400 m, and 200 m). During the rest intervals, isocaloric drinks with the same CHO (6,66-7,0 g), but different sugar (ISO1: 2,46 g; ISO2: 5,6 g; syrup: 6,7 g) and electrolyte content were given in a randomized way. The parameters of running performance, body weight, rating of perceived exertion, heart rate, and blood lactate concentration were analyzed. Results: Over the distances (p=0.10), the results did not show any ergogenic effect of the isotonic drinks in comparison with the syrup-water mixture. There were also no significant differences in terms of rates of perceived exertion (p=0.26) and the physiological parameters of heart rate (p=0.30) and blood lactate (p=0.18) among the groups. Conclusion: During intermittent and repetitive exertion below 30 minutes, homemade energy drinks exhibited the same effects as commercial sports drinks.